2011
DOI: 10.1128/iai.05621-11
|View full text |Cite
|
Sign up to set email alerts
|

Fimbrial Profiles Predict Virulence of Uropathogenic Escherichia coli Strains: Contribution of Ygi and Yad Fimbriae

Abstract: Escherichia coli, a cause of ϳ90% of urinary tract infections (UTI), utilizes fimbrial adhesins to colonize the uroepithelium. Pyelonephritis isolate E. coli CFT073 carries 12 fimbrial operons, 5 of which have never been studied. Using multiplex PCR, the prevalence of these 12 and 3 additional fimbrial types was determined for a collection of 303 E. coli isolates (57 human commensal, 32 animal commensal, 54 asymptomatic bacteriuria, 45 complicated UTI, 38 uncomplicated cystitis, and 77 pyelonephritis). The num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
153
2
2

Year Published

2012
2012
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 126 publications
(158 citation statements)
references
References 55 publications
1
153
2
2
Order By: Relevance
“…EcpD shares $40% homology with the uropathogenic E. coli PapD protein (Raina et al, 1993); it is supposed to be involved in the proper folding of Yad fimbrial proteins and in guiding them to the outer membrane usher in a systematic manner, thereby adding to the growing fimbriae (Korea et al, 2010;Tønjum et al, 1993). Previous studies have shown that the formation of Yad fimbriae is essential for the wild-type level of adhesion to the host epithelial cell, colonization and biofilm formation of UPEC (Spurbeck et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…EcpD shares $40% homology with the uropathogenic E. coli PapD protein (Raina et al, 1993); it is supposed to be involved in the proper folding of Yad fimbrial proteins and in guiding them to the outer membrane usher in a systematic manner, thereby adding to the growing fimbriae (Korea et al, 2010;Tønjum et al, 1993). Previous studies have shown that the formation of Yad fimbriae is essential for the wild-type level of adhesion to the host epithelial cell, colonization and biofilm formation of UPEC (Spurbeck et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Recent studies have shown the importance of yad genes in adherence, as the deletion of yad genes increases cell motility. However, less is known about the fimbriae that are mainly found in UPEC and help in adhesion and infection (Spurbeck et al, 2011). Considering the significant role of EcpD in such a highly orchestrated interplay of molecules, its structural and functional characterization is necessary in order to understand the mechanism of pilus biogenesis and its role in virulence.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…8 UPEC harbor numerous CUP pili systems, the differential expression of which is thought to facilitate colonization of different niches. [9][10][11][12][13] Type 1 pili mediate adherence largely via the FimH tip adhesin, which recognizes and binds mannosylated moieties on biotic and abiotic surfaces. 4,6,[14][15][16][17][18][19][20] Within the host, FimH mediates UPEC binding to the bladder epithelium and is also required for proper formation of biofilm-like intracellular bacterial communities (IBCs) within bladder epithelial cells.…”
mentioning
confidence: 99%
“…Type 1 and P fimbriae represent the two best studied fimbriae present in UPEC. Some of the more recently characterised UPEC fimbriae include F9, type 3-like, Ygi and Yad (Spurbeck et al, 2011, Ulett et al, 2007a, Ong et al, 2008. The genes encoding for fimbriae are always contained within a single operon (Wurpel et al, 2013), and are often phase variable (e.g.…”
Section: Fimbrial Adhesinsmentioning
confidence: 99%